Flow cytometric immunodetection of human immunodeficiency virus type 1 proviral DNA by heminested PCR and digoxigenin-labeled probes. - Yang, G (1994)
PCR is the most sensitive and direct method for detecting blood-borne viruses, as well as an efficient means for producing vector-free probes. However, the application of PCR, especially in the laboratory diagnosis of human immunodeficiency virus (HIV) infection, is impeded by the current use of radiolabeled oligonucleotide probes. Therefore, we have developed a nonisotopic PCR immunoreactive bead (PCR-IRB) assay to detect HIV type 1 proviral DNA from peripheral blood mononuclear cells (PBMC). We used a biotinylated primer in a set of three oligonucleotides selected from the HIV long terminal repeat region for heminested PCR amplification. An internal probe was synthesized by PCR with incorporation of digoxigenin-labeled dUTP. After solution hybridization of the probe with PCR-amplified products (amplicons), the hybridized DNA was captured with streptavidin-coated magnetic beads. For the detection of hybrids, flow cytometric analyses were carried out by two procedures: (i) direct detection with fluorescein isothiocyanate (FITC)-labeled antidigoxigenin immunoglobulin G (IgG) antibody and (ii) indirect detection with antidigoxigenin sheep IgG antibody followed by FITC-labeled anti-sheep IgG antibody. Both procedures in the PCR-IRB assay detected two to three copies of HIV proviral DNA sequences, a sensitivity that is comparable with that of the conventional radioactive detection of amplicons following probe hybridization and electrophoresis. To compare the PCR-IRB assay with the conventional method, we tested 53 pedigreed PBMC specimens from blood donors and newborns; the results obtained were identical. This nonisotopic PCR-IRB assay can also be automated for potential application in laboratory diagnosis of HIV infection, blood bank screening, and therapeutic monitoring of viremia and perinatal transmission.